A diurnal fetal movement pattern: Findings from a cross-sectional study of maternally perceived fetal movements in the third trimester of pregnancy. - Billie F Bradford; Robin S Cronin; Christopher J D McKinlay; John M D Thompson; Edwin A Mitchell; Peter R Stone; Lesley M E McCowan (PLoS ONE, 2019)
Background and objectives Encouraging awareness of fetal movements is a common strategy used to prevent stillbirths. Information provided to pregnant women about fetal movements is inconsistent perhaps due to limited knowledge about normal fetal movement patterns in healthy pregnancies. We aimed to describe maternally perceived fetal movement strength, frequency, and pattern in late pregnancy in women with subsequent normal outcomes. Methods Participants were ≥28 weeks' gestation, with a non-anomalous, singleton pregnancy who had been randomly selected from hospital booking lists and had consented to participate. Fetal movement data was gathered during pregnancy via a questionnaire administered face-to-face by research midwives. Participants remained eligible for the study if they subsequently gave birth to a live, appropriate-for-gestational-age baby at ≥37 weeks. Results Participants were 274 women, with normal pregnancy outcomes. The majority (59.3%, n = 162) of women reported during antenatal interview that the strength of fetal movements had increased in the preceding two weeks. Strong fetal movements were felt by most women in the evening (72.8%, n = 195) and at night-time including bedtime (74.5%, n = 199). The perception of fetal hiccups was also reported by most women (78.8%). Women were more likely to perceive moderate or strong fetal movements when sitting quietly compared with other activities such as having a cold drink or eating. Conclusions Our data support informing women in the third trimester that as pregnancy advances it is normal to perceive increasingly strong movement, episodes of movements that are more vigorous than usual, fetal hiccups, and a diurnal pattern involving strong fetal movement in the evening. This information may help pregnant women to better characterise normal fetal movement and appropriately seek review when concerned about fetal movements. Care providers should be responsive to concerns about decreased fetal movements in the evening, as this is unusual.